Empowering women in agriculture: The role of the WEAI in Bangladesh - Ahmed, Akhter; Bakhtiar, M. Mehrab; Quisumbing, Agnes R.; Malapit, Hazel J.; Ghostlaw, Julie (International Food Policy Research Institute, 2023)
Empowering women is crucial for a country's development because it leads to greater economic growth, increased productivity, and improved social outcomes. When women have access to education, economic opportunities, and decision-making power, they are better able to contribute to their families and communities. This can lead to increased income, improved health and education outcomes, and reduced poverty. In Bangladesh, women and girls still face considerable barriers to accessing education and economic opportunities, and are often subjected to traditional gender roles that may hinder them. Although women play a crucial role in agriculture, they experience many challenges that limit their productivity and economic potential, such as limited access to credit and training. They are also often marginalized and excluded from decision-making processes. As the complexity and importance of gender equity in development work has increased, so too has the need to measure empowerment and progress made toward improving empowerment and achieving gender parity. In Bangladesh, there has been growing momentum by the government and development partners to use evidence to inform gender-sensitive and -responsive policies and programs. The Women's Empowerment in Agriculture Index (WEAI) has emerged as a key tool to achieve this objective. This brief examines how WEAI data have informed and supported the design of policies and programs to promote women's empowerment in Bangladesh.